Begonia caramoanensis (sect. Baryandra, Begoniaceae) a new species from Camarines Sur, Philippines - Rubite, Rosario R.; Irabagon, Madeleine L.; Palacio, Diane Joy E.; Ang, Yu Pin; Bustamante, Rene Alfred Anton (Phytotaxa, 2020)
Begonia caramoanensis from Caramoan, Camarines Sur, Luzon Island is described as a new species endemic to the Philippines. This is the latest addition to the species rich Begonia section Baryandra. It resembles Begonia madulidii but is distinguished by the dark green almost orbicular leaves; extensive inflorescence branching five times; and the glandular hairs of the bracts, peduncle, pedicels and ovary. More than 500 individuals, were observed in each of the four barangays of Caramoan, thus according to to the IUCN red list categories and criteria, B. caramoanensis is hereby proposed to be placed under Least Concern (LC) category.